2016
DOI: 10.1177/0897190016628960
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison of Acute Kidney Injury During Treatment With the Combination of Piperacillin-Tazobactam and Vancomycin Versus the Combination of Cefepime or Meropenem and Vancomycin

Abstract: The result of this study suggests that the risk of developing AKI is increased in patients receiving the combination of piperacillin-tazobactam and vancomycin versus those receiving the combination of cefepime or meropenem and vancomycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
43
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 17 publications
8
43
1
Order By: Relevance
“…A prospective open‐label cohort compared the incidence of AKI in patients receiving VAN/PTZ with those receiving VAN/CEF or VAN/MER. This study demonstrated a significantly higher incidence of AKI in the VAN/PTZ group . A retrospective cohort study evaluated the risk of AKI in patients receiving VAN/PTZ compared with VAN/MER but did not detect a statistically significant difference between study groups .…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…A prospective open‐label cohort compared the incidence of AKI in patients receiving VAN/PTZ with those receiving VAN/CEF or VAN/MER. This study demonstrated a significantly higher incidence of AKI in the VAN/PTZ group . A retrospective cohort study evaluated the risk of AKI in patients receiving VAN/PTZ compared with VAN/MER but did not detect a statistically significant difference between study groups .…”
mentioning
confidence: 65%
“…Most of these studies assessed the risk of AKI in patients receiving VAN/PTZ versus VAN monotherapy or VAN/cefepime (CEF). Three studies compared the incidence of AKI in patients receiving VAN/PTZ versus VAN/MER, and the results were discordant . A prospective open‐label cohort compared the incidence of AKI in patients receiving VAN/PTZ with those receiving VAN/CEF or VAN/MER.…”
mentioning
confidence: 99%
“…Ten of these studies compared vancomycin + piperacillin‐tazobactam with vancomycin alone, four compared vancomycin + piperacillin‐tazobactam with vancomycin + β‐lactam, and one study compared vancomycin + piperacillin‐tazobactam with vancomycin alone or vancomycin + other antibiotics. Six of the 15 studies were abstracts, and 9 were published in full text . Of the four studies that compared vancomycin + piperacillin‐tazobactam with vancomycin + β‐lactam, three used cefepime as a control, and one used both cefepime and meropenem .…”
Section: Resultsmentioning
confidence: 99%
“…Piperacillin‐tazobactam alone has rarely been associated with AKI . Case reports of AKI secondary to piperacillin‐tazobactam alone suggest that acute interstitial nephritis is the most likely cause . Piperacillin‐tazobactam and vancomycin are often used in combination to treat health care–associated infections.…”
mentioning
confidence: 99%
“…16,17 The combined use of VAN and a broad-spectrum β-lactam antibiotic is used as an initial empiric antimicrobial therapy in suspected severe healthcare-associated infections whenever it is necessary to cover both methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa. 19 Another study involving adults found higher rates of AKI in patients receiving VPT than in those receiving the combination of VAN and meropenem (VM) (16.5% vs 3.6%, P = 0.009), with the median time to AKI onset being significantly shorter in the former group (3 vs 7 days, P = 0.009). Surprisingly, the incidence of AKI was found to be significantly higher among children receiving VAN and PT (VPT) than in those receiving VAN alone or a combination of VAN and another β-lactam antibiotic, although reported nephrotoxicity rates of PT have been low when used as a monotherapy (<1%).…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%